Anti-inflammatory role of sympathetic nerves in chronic intestinal inflammation. Issue 7 (28th February 2008) - Straub, R H; Grum, F; Strauch, U; Capellino, S; Bataille, F; Bleich, A; Falk, W; Schölmerich, J; Obermeier, F
Abstract : Background: Substance P (SP) is a pro-inflammatory neuropeptide in colitis, whereas sympathetic neurotransmitters are anti-inflammatory at high concentrations. Aim and methods: In all layers of the colon, nerve fibre densities of SP + and sympathetic nerve fibres were investigated (22 Crohn's disease, six diverticulitis, and 22 controls). In addition, the nerve fibre repellent factor semaphorin 3C (SEMA3C) was studied. The functional role of the sympathetic nervous system was tested in dextran sodium sulfate (DSS) and Il10 −/− colitis. Results: In all layers, Crohn's disease patients demonstrated a loss of sympathetic nerve fibres. Sprouting of SP + nerve fibres was particularly observed in the mucosa and muscular layer in Crohn's disease. SEMA3C was detected in epithelial cells, and there was a marked increase of SEMA3C-positive crypts in the mucosa of Crohn's disease patients compared to controls. In Crohn's disease, the number of SEMA3C-positive crypts was negatively related to the density of mucosal sympathetic nerve fibres. Sympathectomy reduced acute DSS colitis but increased chronic DSS colitis. Sympathectomy also increased chronic colitis in Il10 −/− mice. Conclusions: This study demonstrated a loss of sympathetic and an increase of SP + nerve fibres in Crohn's disease. SEMA3C, a sympathetic nerve repellent factor, is highly expressed in the epithelium of Crohn's disease patients. In chronic experimental colitis, the sympathetic nervous system confers an anti-inflammatory influence. Thus, the loss of sympathetic nerve fibres in the chronic phase of the disease is most probably a pro-inflammatory signal, which might be related to repulsion of these fibres by SEMA3C and other repellents.